Pemphigus Vulgaris: A Rare Case of Gingival Involvement - Thakur, Nisha (Contemp Clin Dent, 2020)
Pemphigus vulgaris (PV) is an autoimmune mucocutaneous disease characterized by epithelial blistering affecting the mucosal/cutaneous surfaces. This case report demonstrates the oral manifestations of PV in the uncommon locations such as the attached, marginal, and interdental gingiva with no involvement of oral mucosa, tongue, palate, or buccal mucosa.